2021
DOI: 10.1016/j.euo.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Trends from Urologic Cancers in Europe over the Period 1980–2017 and a Projection to 2025

Abstract: Background: Patterns and trends in urologic cancer mortality still show geographical differences across Europe. Objective: To monitor mortality trends from urologic cancers, including prostate, testis, bladder, and kidney cancers, in Europe. Design, setting, and participants: We carried out a time-trend analysis for 36 European countries using the official World Health Organization database. Outcome measurements and statistical analysis: We extracted the number of deaths and population data over the 1980-2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 47 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…It is important to evaluate current global epidemiological trends of testicular cancer, such that country-or age-specific preventive strategies can be implemented. Prior studies on testicular cancer had found a decline in mortality among European countries in the past few decades [20] and an increase in incidence globally, with the gap between highand low-incidence countries closing up [21]. However, these were limited to specific countries/region, used historical data, and did not conduct the risk factor analysis by country level [1,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to evaluate current global epidemiological trends of testicular cancer, such that country-or age-specific preventive strategies can be implemented. Prior studies on testicular cancer had found a decline in mortality among European countries in the past few decades [20] and an increase in incidence globally, with the gap between highand low-incidence countries closing up [21]. However, these were limited to specific countries/region, used historical data, and did not conduct the risk factor analysis by country level [1,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies on testicular cancer had found a decline in mortality among European countries in the past few decades [20] and an increase in incidence globally, with the gap between highand low-incidence countries closing up [21]. However, these were limited to specific countries/region, used historical data, and did not conduct the risk factor analysis by country level [1,[20][21][22][23]. This study investigated the most recent global incidence, mortality, risk factors, and temporal trends of testicular cancer by country and age group, using information from global cancer registries and risk factor databases.…”
Section: Introductionmentioning
confidence: 99%
“…Effective organized population-based BC screening programmes, implemented in many Northern and Western European countries in the late 1980s, have been related to the reduced BC mortality; whereas the role of extensive opportunistic prostate-specific antigen (PSA)-based testing for PC remains uncertain [ 1 , 2 , 4 – 9 ]. In Central and Eastern Europe, modest and late decreases or the continued increase in BC and PC mortality was observed; unfavourable trends remain largely unexplained and are only partly attributable to less accessible or delayed modern effective treatment [ 1 3 , 5 , 9 11 ]. Similar epidemiological features have been shown between BC and PC, implying common causal pathways, including hormonal, metabolic, genetic, dietary and other factors [ 6 , 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Western and Northern European countries, although PC incidence trends increased, mortality rates have been declining since the 1990s [ 6 , 7 , 15 ]. In Central and Eastern Europe declines in mortality trends started later and were less pronounced [ 1 , 3 , 10 , 16 ]. It has been shown that repeated PC screening using PSA testing reduces PC mortality risk by 20% [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation